Un oggetto del culto ittita: (giš)zaḫurti - Polvani, Anna Maria (Fs Pugliese Carratelli)
KUB XI 34 V 38-50; KUB XI 13 II 1 18:1-18; KUB XX 11 II 7-14; KВо XX 85 III 3'-7'; KВо XXV 41 Rs 13; KВо XX 32 III 4'-12'; KUB XLII 107 IV? 1-17.